Health system governance for the integration of mental health services into primary health care in the Sub-Saharan Africa and South Asia Region: a systematic review - Abdul Rahim, Arifah; Abdul Manaf, Rosliza; Juni, Muhamad Hanafiah; Ibrahim, Normala (SAGE Publications, 2021)
Governance has been highlighted as an important building block underpinning the process of mental health integration into primary healthcare. This qualitative systematic review aims to identify the governance issues faced by countries in the Sub-Saharan Africa and South Asia Region in the implementation of integrated primary mental healthcare. PRISMA guideline was used to conduct a systematic search of relevant studies from 4 online databases that were filtered according to inclusion and exclusion criteria. Using the Critical Appraisal Skills Program (CASP) Qualitative Checklist, a quality appraisal of the selected articles was performed. By drawing upon institutional theory, data was extracted based on a pre-constructed matrix. The CERQual approach synthesized evidence and rank confidence level as low, moderate or high for 5 key findings. From 567 references identified, a total of 8 studies were included. Respondents were policymakers or implementers involved in integrated primary mental healthcare from the national, state, and district level. Overall, the main governance issues identified were a lack of leadership and mental health prioritization; inadequate financing and human resource capacity; and negative mental health perceptions/attitudes. The implication of the findings is that such issues must be addressed for long-term health system performance. This can also improve policymaking for better integration of primary mental health services into the health systems of countries in the Sub-Saharan and South Asia region.